Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $e$ be an idempotent of a ring $A$ and $N$ is an $A$-module. Why $\mathrm{Hom}_{eAe}(A,N)=\mathrm{Hom}_{eAe}(Ae,N), N\otimes_{eAe}A=N\otimes_{eAe}eA$? Can you prove this explicitly? Is the following true:

  • $\mathrm{Hom}_{eAe}(A,N)=\mathrm{Hom}_{eAe}(eA,N)$
  • $N\otimes_{eAe}A=N\otimes_{eAe}Ae$
  • $\mathrm{Hom}_{eAe}(A,N)=\mathrm{Hom}_{eAe}(A,eN)$
  • $N\otimes_{eAe}A=Ne\otimes_{eAe}A$
  • $\mathrm{Hom}_{eAe}(A,N)=\mathrm{Hom}_{eAe}(A,Ne)$
  • $N\otimes_{eAe}A=eN\otimes_{eAe}A$

Thank you.

share|cite|improve this question
up vote 2 down vote accepted

hint: $A = eA \oplus (1-e)A$ as right $A$-modules, but also as left $eAe$-modules. $eAe$ acts as zero on the second summand. This should help you write down the isomorphisms.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.